Sredstva vosstanovleniya i adaptatsiya k nagruzkam v protsesse presorevnovatel'noi podgotovki bortsov - Tarasenko, M. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Article describes the means and methods of reinforcement and wrestlers' adaptation to loads during pre-competition period and compares different methods which were used (i.g. different physiotherapeutic means).